\(x\sqrt{x}+y\sqrt{y}+2x\sqrt{y}+2y\sqrt{x}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 7 2019

\(x\sqrt{x}+y\sqrt{y}+2x\sqrt{y}+2y\sqrt{x}\)

\(=\left(\sqrt{x^3}+\sqrt{y^3}\right)+\left(2x\sqrt{y}+2y\sqrt{x}\right)\)

\(=\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{xy}+y\right)+2\sqrt{xy}\left(\sqrt{x}+\sqrt{y}\right)\)

\(=\left(\sqrt{x}+\sqrt{y}\right)\left(x+\sqrt{xy}+y\right)\)

\(\hept{\begin{cases}\sqrt{2x+3}+x^2+2x=\sqrt{2y-1}+y^2-2y\left(1\right)\\\sqrt{x-2}+\sqrt{y-1}=3\left(2\right)\end{cases}}\)

\(Đkxđ:x\ge2;y\ge1\)

\(\left(1\right)\Leftrightarrow\sqrt{2x+3}-\sqrt{2y-1}=y^2-x^2-2\left(y+x\right)\)

\(\frac{2x-2y+4}{\sqrt{2x+3}+\sqrt{2y-1}}=\left(x+y\right)\left(y-x\right)-2\left(y+x\right)\)

\(\Leftrightarrow\frac{2\left(x-y+2\right)}{\sqrt{2x+3}+\sqrt{2y-1}}+\left(x+y\right)\left(x-y+2\right)=0\)

\(\Leftrightarrow\left(x-y+2\right)\left(\frac{2}{\sqrt{2x+3}+\sqrt{2y-1}}+x+y\right)=0\)

\(\Leftrightarrow x-y+2=0\)

\(\Leftrightarrow x=y-2\)

Thay vào \(\left(2\right)\) ...................................................................

6 tháng 10 2019

b,ĐK:\(-3\le x\le\frac{3}{2}\)

\(PT\Leftrightarrow x-1+4\left(\sqrt{x+3}-2\right)+2\left(\sqrt{3-2x}-1\right)=0\)

\(\Leftrightarrow x-1+\frac{4\left(x-1\right)}{\sqrt{x+3}+2}+\frac{2\left(2-2x\right)}{\sqrt{3-2x}+1}=0\)

\(\Leftrightarrow\left(x-1\right)\left(1+\frac{4}{\sqrt{x+3}+2}-\frac{4}{\sqrt{3-2x}+1}\right)=0\)

Với \(x\ge-3\) \(\Rightarrow\frac{4}{\sqrt{x+3}+2}>0\) và \(3-2x\le9\Rightarrow-\frac{4}{\sqrt{3-2x}+1}\ge-1\)

\(\Rightarrow1+\frac{4}{\sqrt{x+3}+2}-\frac{4}{\sqrt{3-2x}+1}>0\)

\(\Rightarrow x-1=0\Rightarrow x=1\)(tm)

6 tháng 10 2019

c,Đk: \(x\ge2,y\ge3,z\ge5\)

pt <=> \(x-2\sqrt{x-2}+y-4\sqrt{y-3}+z-6\sqrt{z-5}+4=0\)

<=> \(\left(x-2\right)-2\sqrt{x-2}+1+\left(y-3\right)-4\sqrt{y-3}+4+\left(z-5\right)-6\sqrt{z-5}+9=0\)

<=>\(\left(\sqrt{x-2}-1\right)^2+\left(\sqrt{y-3}-2\right)^2+\left(\sqrt{z-5}-3\right)^2=\)0

=>\(\left\{{}\begin{matrix}\sqrt{x-2}-1=0\\\sqrt{y-3}-2=0\\\sqrt{z-5}-3=0\end{matrix}\right.\) <=> \(\left\{{}\begin{matrix}x=3\\y=7\\z=14\end{matrix}\right.\)(t/m)

d, \(2x+2y+2z=\sqrt{4x-1}+\sqrt{4y-1}+\sqrt{4z-1}\left(đk:x,y,z\ge\frac{1}{4}\right)\)

<=> \(4x+4y+4z=2\sqrt{4x-1}+2\sqrt{4y-1}+2\sqrt{4z-1}\)

<=> \(\left(4x-1\right)-2\sqrt{4x-1}+1+\left(4y-1\right)-2\sqrt{4y-1}+1+\left(4z-1\right)-2\sqrt{4z-1}+1=0\)

<=>\(\left(\sqrt{4x-1}-1\right)^2+\left(\sqrt{4y-1}-1\right)^2+\left(\sqrt{4z-1}-1\right)^2=0\)

=>\(\left\{{}\begin{matrix}\sqrt{4x-1}-1=0\\\sqrt{4y-1}-1=0\\\sqrt{4z-1}-1=0\end{matrix}\right.\) <=> \(\left\{{}\begin{matrix}x=\frac{1}{2}\\y=\frac{1}{2}\\z=\frac{1}{2}\end{matrix}\right.\)(tm)

26 tháng 8 2017

Bài 1 m bình phương 2 vế